Fascination for Genetically Colored Cottons - Narayanan, S. S.; Maiti, Ratikanta; Vidyasagar, P. (International Journal of Bio-resource and Stress Management, 2010)
The article provides an insight into the history and development of genetically colored cotton in the world. Though extensively grown and used in the past, after industrial revolution short-fibered colored cotton was replaced by long-fibered white linted cotton processed better in the industrial looms. However, the cultivation of commercial white cotton is pesticide dependant. Moreover, its processing involves the use of chlorine-bleaching agents, formaldehydes and phenols quite harmful and dangerous to human and other life forms. The naturally colored varieties were almost going to extinct until Sally Fox, a graduate from University of California in Integrated Pest Management, rediscovered brown cotton seeds in 1982. She branded her discovery as Fox Fiber-strong long-fibered colored cotton which increased its color intensity with repeated washing. In India, cultivation of the colored cotton and its use did not receive encouragement for various reasons. It may be environment friendly, aesthetic and fascinating, but its continued patronage will be determined by economic outlook and long-term benefits.